A survey on the awareness of pet owners towards the pet food label - Sivananthan, Dinaesh Kumar (2018)
Pet food label is a legal document regulated by the Association of American Feed Control Officials (AAFCO) and is the primary means of communication between the pet food manufacturers and pet owners. There are several aspects such as the awareness on the different type of food categories, ingredients, feeding guide and packaging labels that should be known by the pet owners to ensure they deliver the precise amount and type of nutrients required by their pet. Indeed, balance nutrients provided at a specific age and life stage of the pet is important to ensure proper development and growth. The objective would be to determine the level of awareness of pet owners on the pet food label and to determine the factors contributing to the awareness of the pet food label. The pet food label may be taken for granted but it has major effect of the overall well-being of the animal's health. Therefore, to better understand the level of awareness of pet owners on the pet food label, a survey was conducted in which 150 pet owners were given a set of questionnaire adapted from The University of Glasgow‟s research study. The data was analyzed using a descriptive manner and then tabulated in SPSS. Results showed that, the awareness of pet owners on the pet food label is low and the factors contributing to the awareness of pet food label are customer review charts, fancy and illustrative pictures, simple and direct information, attractive colors of packaging and font size but the main contributing factors to the awareness of pet owners on the pet food label would be improper usage of font size and customer review charts. In conclusion, this study shows that the low awareness of pet food label among pet owners can lead to serious health issues of their pet in the future.